The Impact of Digital Media on Student Learning at University - Hirnanda Dimas Pradana (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2023)
This research aims to improve students' perceptions of the utility and practicability of obtaining information using digital media. 102 students engaged in a survey for data collection purposes. According to a study's findings, most students see the use of digital media in the classroom as a clever and easy instructional strategy. Several factors must be addressed to improve the educational process's utility and efficacy, such as the calibre of instructional materials, the availability and amount of technological equipment, and the trainers' assistance. Digital media have made possible an educational process that necessitates using supplementary resources to address issues. In conclusion, the employment of digital media in the educational process is lauded as a practical and less labour-intensive technique. However, parental and other assistance is required, as well as other factors that impact the experience's comfort and efficacy.